Interleukin-1β expression on periodontitis patients in Surabaya - Chiquita Prahasanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Periodontal disease, commonly known as periodontitis is an infectious disease which has multifactorial etiologic factors. It may affect everybody in any ages with no gender nor sex predilection and usually can be detected under routine clinical examination. This disease is a manifestation of local factors, host factor and environmental factors, resulting in periodontal tissue damage which may cause tooth mobility and tooth loss. Interleukin-1 is a pro-inflammatory protein which functions primarily as inflammatory mediator in host innate immune responses. IL-1 is a regulator, affecting many biological activities including proliferation, development, homeostasis, regeneration, repair and inflammation which contribute to tissue damage and alveolar bone resorption. Purpose: This research was aimed to reveal the basic pathogenesis of periodontitis and could determine the future definitive treatment for patients with periodontitis. Methods: Data were obtained from 40 patients with aggressive periodontitis and 40 patients with chronic periodontitis. Samples were collected from periodontal tissue patients and protein expression of IL-1β was performed with immunohistochemistry. Results: Most female patient suffer aggressive periodontitis and chronic periodontitis. The datas were analyzed with t-test. The t values result was -8623, significance 0.001, with α = 5%, which indicated there was significant difference in IL-1β expression between aggressive and chronic periodontitis. The box plot diagram showed marked difference in distribution of protein expression of IL-1β between patients with aggressive periodontitis and chronic periodontitis. With a regression equation, it might be concluded that the protein expression of IL-1β might affect the incidence of aggressive periodontitis and chronic periodontitis. The OR value was calculated for 0.746 (sign.= 0.001), which indicate each increment of one unit protein expression of IL-1β will lead the risk for Aggressive periodontitis 0.746 times higher or if the protein expression of respondents increased one unit, the risk of chronic IL-1β periodontitis may be 1.34 times higher. Conclusion: This study elucidated that the elevation proteins expression of IL-1β in patients with chronic periodontitis demonstrated this cytokine as an indicator of inflammation.Latar belakang: Penyakit periodontal yang biasa dikenal dengan periodontitis adalah penyakit infeksi, yang disebabkan oleh berbagai faktor, dapat menyerang setiap orang tanpa membedakan usia dan gender serta mudah ditemukan pada pemeriksaan klinis oleh seorang dokter gigi. Penyakit ini merupakan manifestasi dari interaksi antara faktor lokal dengan faktor lingkungan, yang berakibat pada kerusakan jaringan periodontal, dapat mengakibatkan terjadinya kegoyangan gigi hingga tanggalnya gigi. Interleukin-1 merupakan protein pro-inflamatori dengan fungsi utama sebagai mediator respon inflamasi pejamu pada sistem imunitas innate. Interleukin-1 merupakan regulator, dimana memainkan peranan pada sejumlah aktivitas biologic termasuk proliferasi, pengembangan, homeostasis, regenerasi, repair dan keradangan berperan pada kerusakan jaringan ikat serta resorpsi tulang alveolar. Tujuan: Penelitian ini bertujuan untuk menentukan dasar patogenesa periodontitis dan dapat digunakan sebagai dasar perawatan penderita periodontitis pada masa mendatang. Metode: Data penelitian didapat dari 40 penderita dengan periodontitis agresif dan 40 penderita periodontitis kronis. Sampel berasal dari jaringan yang mengalami kelainan periodontal dan uji ekspresi protein IL-1β dilakukan secara imunohistokimia. Hasil: Penderita yang mengalami kelainan pada penelitian ini sebagian besar adalah perempuan baik periodontitis agresif maupun periodontitis kronis. Uji statistik yang digunakan adalah uji-t diperoleh nilai t sebesar -8.623 dan signifikansi 0.001, dengan α = 5% maka terdapat perbedaan bermakna ekspresi protein IL-1β antara penderita periodontitis agresif dan penderita periodontitis kronis. Diagram box plot memperlihatkan sebaran ekspresi protein IL-1β antara penderita periodontitis agresif dan penderita periodontitis kronis yang tampak sangat jauh berbeda. Ekspresi protein IL-1β berpengaruh pada kejadian penderita periodontitis agresif dan penderita periodontitis kronis, dengan bentuk persamaan regresi. Nilai estimasi OR untuk variabel ekspresi protein IL-1β adalah 0,746 (sign. = 0,00). Artinya, jika ekspresi protein IL-1β responden bertambah satu satuan, maka risiko terjadinya periodontitis agresif menjadi 0,746 kali atau jika ekspresi protein IL-1β responden bertambah satu satuan, maka risiko terjadinya periodontitis kronis menjadi 1,34 kali. Kesimpulan: Ekspresi protein Il-1β yang meningkat pada penderita periodontitis kronis menujukkan bahwa sitokinini merupakan indikator pada keadaan keradangan.